Discovery of a Mesolithic burial near the painted rock-shelter of Ban Tha Si (Lampang province, Northern Thailand): Implications for regional mortuary practices - Valery Zeitoun (2018)
Although the oldest Neolithic cultures in eastern Asia have for the most part been documented in China and Vietnam, a large number of Early Metal Age sites have been reported in northeastern Thailand. On the other hand, the Hoabinhian, principally identified by its characteristic unifacial tools, is known throughout the Late Pleistocene up until 3000. BP and is spread across the whole of continental Southeast Asia. The chronology of Hoabihnian lithic assemblages is still poorly documented and burials from the period are scarce and often do not provide enough information to allow the evolution of regional mortuary practices to be investigated. Here we describe a burial dated to 7047. ±. 53. BP found associated with a Hoabinhian stone tool assemblage and fauna near the painted rock-shelter of Ban Tha Si. This discovery provides important new chrono-cultural information for continental Southeast Asia, especially with regard to changing regional mortuary practices. Alors que les cultures du Néolithique ancien d'Asie orientale ont essentiellement été décrites en Chine et au Vietnam, les cultures de l'âge des Métaux ont abondamment été documentées dans le Nord-Est de la Thaïlande. Par ailleurs, le Hoabinhien, principalement identifié par ses outils unifaciaux caractéristiques,est connu du Pléistocène tardif jusque vers 3000. BP sur l'ensemble du Sud-Est asiatique continental. La chronologie des assemblages lithiques hoabinhiens reste encore peu documentée et les sépultures de cette période sont rares et ne procurent ainsi que peu d'information permettant de suivre l'évolution des pratiques funéraires. Nous décrivons ici une sépulture inédite qui a été datée de 7047. ±. 53. BP et qui est associée à un assemblage lithique hoabinhien dans l'abri-sous-roche orné de Ban Tha Si. Cette découverte apporte des informations chronoculturelles nouvelles pour l'Asie du Sud-Est continental et permet de dresser un premier panorama de l'évolution des pratiques funéraires de cette période. © 2012 Académie des sciences.